2006
DOI: 10.1038/sj.pcan.4500923
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality-of-life after external beam radiation therapy for localized prostate cancer: intensity-modulated radiation therapy versus conformal radiation therapy

Abstract: We compared health-related quality-of-life (HRQL) after intensity-modulated radiotherapy (IMRT) with statuses obtained after old and new protocols of three-dimensional conformal radiation therapy (3DCRT) for localized prostate cancer. We measured the general and disease specific HRQL using the MOS 36-Item Health Survey (SF-36), and the University of California, Los Angeles Prostate Cancer Index (UCLA PCI), respectively. IMRT resulted in similar profiles of general and disease-specific HRQL to two other methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In a prospective longitudinal study, Lips et al (9) compared QoL after 70 Gy of 3D-CRT with QoL after 76 Gy of intensity-modulated RT (IMRT) in patients with prostate cancer and concluded that IMRT seems to provide the possibility of escalating the RT dose without deterioration in QoL. The same conclusions were drawn by Yoshimura et al (10) and Kupelian et al (11) after 1 and 2 years of follow-up, respectively, in patients treated with IMRT to a relatively high dose. However, it is not fair to compare these studies with our study, because these studies are not randomized, the radiation dose was on average lower than 78 Gy, the follow-up was short (6, 12, and 24 months, respectively), and the number of patients was small (92, 60, and 51 patients, respectively).…”
Section: Discussionmentioning
confidence: 54%
“…In a prospective longitudinal study, Lips et al (9) compared QoL after 70 Gy of 3D-CRT with QoL after 76 Gy of intensity-modulated RT (IMRT) in patients with prostate cancer and concluded that IMRT seems to provide the possibility of escalating the RT dose without deterioration in QoL. The same conclusions were drawn by Yoshimura et al (10) and Kupelian et al (11) after 1 and 2 years of follow-up, respectively, in patients treated with IMRT to a relatively high dose. However, it is not fair to compare these studies with our study, because these studies are not randomized, the radiation dose was on average lower than 78 Gy, the follow-up was short (6, 12, and 24 months, respectively), and the number of patients was small (92, 60, and 51 patients, respectively).…”
Section: Discussionmentioning
confidence: 54%
“…The diVerences in outcomes between these reports and our Wndings may result from several factors, including diVerent patient characteristics such as age at analysis, periods of follow-up and duration of hormonal therapy. Another explanation is that sexual distress of Japanese men who received EBRT showed no alteration before and after treatment (Yoshimura et al 2007). Japanese men reported less sexual activity than American men, but Japanese men were less likely to be bothered (Namiki et al 2008).…”
Section: Discussionmentioning
confidence: 97%
“…1,[3][4][5][6] Symptoms are most severe within approximately 3 months after treatment, and then slowly improve. 3,[7][8][9] Many patients continue to experience symptoms 1-2 years later. 1,3,4,6,7,10,11 Pain, fatigue, and physical and social function are also affected.…”
Section: Introductionmentioning
confidence: 99%